Integrated summary of immunogenicity of polatuzumab vedotin in patients with relapsed or refractory B-cell non-Hodgkin’s lymphoma - Randall C. Dere; Richard L. Beardsley; Dan Lu; Tong Lu; Grace H-W. Ku; Gabriel Man; Van Nguyen; Surinder Kaur (Frontiers in Immunology, 2023)
Polatuzumab vedotin, marketed under the trade name POLIVY®, is a CD79b-targeted antibody-drug conjugate that preferentially delivers a potent anti-mitotic agent (monomethyl auristatin E) to B cells, resulting in anti-cancer activity against B-cell malignancies. In 2019, polatuzumab vedotin in combination with rituximab and bendamustine was approved by the United States Food and Drug Administration for the treatment of adult patients with diffuse large B-cell lymphoma who have received at least two prior therapies. Recent Health Authority guidance recommendations for submitting an Integrated Summary of Immunogenicity were followed including a comprehensive immunogenicity risk assessment, bioanalytical strategy, and immunogenicity data to support the registration of polatuzumab vedotin. Key components of the polatuzumab vedotin Integrated Summary of Immunogenicity and data are presented. Validated semi-homogeneous bridging enzyme-linked immunosorbent assays were used to detect anti-drug antibodies (ADA) to polatuzumab vedotin and characterize the immune response in patients with non-Hodgkin’s lymphoma. The overall incidence of ADA observed for polatuzumab vedotin was low across seven clinical trials. The low incidence of ADA is likely due to the mechanism of action of polatuzumab vedotin that involves targeting and killing of B cells, thereby limiting the development to plasma cells and ADA secretion. Furthermore, patients are co-medicated with rituximab, which also targets B cells and results in B-cell depletion. Therefore, the immunogenicity risk is considered low and not expected to impact the polatuzumab vedotin benefit/risk profile.